PEMANFAATAN POJOK BACA SEBAGAI SUMBER BELAJAR DALAM MENINGKATKAN PEMAHAMAN IPS SISWA KELAS VIII DI SMP NEGERI 19 KOTA BENGKULU - Jesi Veronika; Salamah; M. Ilham Gilang (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2026)
This study aims to describe the management, utilization, and challenges encountered in using reading corners as a learning resource to improve the understanding of Social Studies (IPS) among eighth-grade students at SMP Negeri 19 Kota Bengkulu. This research employed a qualitative approach with a descriptive design. Primary data were obtained through interviews with students, teachers, and reading corner managers, as well as direct observation and documentation. Secondary data were collected from literature, school documents, and previous related studies. Data collection techniques included observation, interviews, and documentation, while data analysis was carried out through data reduction, data display, and conclusion drawing. The findings indicate that the management of reading corners was implemented through curriculum-based planning, the organization of reading collections, the implementation of reading activities with teacher guidance, and evaluations that remain informal. The utilization of reading corners has been proven to enhance students’ understanding of Social Studies through directed reading activities, group discussions, and the use of contextual reading materials. The challenges identified include limited book collections, insufficient supervision, and low reading motivation among some students. The use of reading corners contributes positively to improving the Social Studies comprehension of eighth-grade students at SMP Negeri 19 Kota Bengkulu. Therefore, optimizing reading corners through better management, a more diverse collection of reading materials, and strategies to enhance student motivation is necessary to maximize their benefits